The measurement of changes in tropical rangelands ecosystems - Bille, Jean-Claude (Australian Academy of Science, 1986)
Discusses the results of the measurement of environmental changes in grazed ecosystems with reference to correlated changes in livestock management in Kenya; includes techniques used to measure the changes, and proposed methods; presents data on a case study at a group ranch located in western Kenya which covers 50,000 ha.; ends with comparison of surveys, i.e., that of 1978 and 1981.